Connective tissue disease associated interstitial pneumonia: a challenge for both rheumatologists and pulmonologists. - Geerts, Sarah; Wuyts, Wim; De Langhe, Ellen; Lenaerts, Jan; Yserbyt, Jonas (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Interstitial lung disease (ILD) can be either idiopathic, the result of exposure or may be associated with extrapulmonary diseases. Among the latter, connective tissue diseases (CTDs) make up the largest part. The identification, follow-up and treatment of CTD-associated ILD (CTD-ILD) are a challenge for every physician as ILD can occur before, during and after the diagnosis of CTD. Early detection of pulmonary involvement is an essential task for the treating rheumatologist and recognition of the underlying CTD can pose a challenge for the treating pulmonologist. Multidisciplinary engagement towards the patient is therefore indispensable for optimal clinical care.